Exploring the Attitudes of the Digital Age Academic Community in Responding to Issues in Social Harmonization Education at State Islamic University - Mawardi Lubis; Alfauzan Amin; Alimni Alimni (STAI Hubbulwathan Duri, 2023)
The research subject pertains to the attitude of the academic community in the digital era towards addressing the issue of social harmonisation education at a State Islamic University in Bengkulu. Meanwhile, the purpose of this study is to obtain a description of the response of the digital era academic community to the issue of social harmonization education. Based on this description, it is hoped that recommendations can be compiled related to how to improve the response of the digital era academic community to the issue of social harmonization education. The study was conducted in August-September 2022 at Fatmawati Sukarno State Islamic University (UIN FAS) Bengkulu with a quantitative type of research using survey methods. Data analysis techniques are used using descriptive quantitative analysis techniques with the help of percentage formulations (P = f / N x 100) and to determine the response categories used TSR formulations (High, Medium, and Low). The population of this study was all lecturers, employees, and students of Fatmawati Sukarno State Islamic University (UIN FAS) Bengkulu who joined the WhatsApp Group totalling 390 people as well as being respondents to the study. The results showed that the response of the digital era academic community to the issue of social harmonization education was in the low category (25.64%).